KAPASITAS PETANI DALAM MEWUJUDKAN KEBERHASILAN USAHA PERTANIAN: KASUS PETANI SAYURAN DI KABUPATEN PASURUAN DAN KABUPATEN MALANG PROVINSI JAWA TIMUR - Herman S.; Sumardjo Sumardjo; Pang S. Asngari; Prabowo Tjitropranoto; Djoko Susanto (Jurnal Penyuluhan, 2008)
Farmer’s capacity is the most important factor in agricultural development based on human resources; high level of farmer’s capacity ensures his success and sustainable of agribusiness. The objectives of the research are: to determine the level of farmer’s capacity and to analyze dominant factors affecting farmer’s capacity. The research was carried out in Malang and Pasuruan Districts which are the centres of vegetables in East Java Province. Data were collected using structured interviews and direct observation. Total sample was consisted of 177 farmers, drawn using a cluster random sampling technique. The results of the research show that: the level of farmer’s capacity is in a lows level, there is significant difference of the level of farmer’s capacity in two locations, The level of farmer’s capacity in Malang district is higher than in Pasuruan District. The characteristics of innovation and formal educational are determinant factors affecting farmer’s capacity. The fasctors have significant indirect effect to the success of agribussiness through farmer’s capacity and self reliance in farming. The results of the research imply that agricultural extension should take into consideration the level of farmer’s educational level, farmer’s capacity and characteristics of innovation in developing programs to disseminate innovation and information.